HETEROTIC POTENTIAL OF UPLAND COTTON HYBRIDS FOR EARLINESS AND YIELD RELATED ATTRIBUTES - IMTIAZ, M; SHAKEEL, A; NASIR, B; KHALID, MN; AMJAD, I (Biological and Clinical Sciences Research Journal, 2022)
Cotton is a long duration crop which effects the timely sowing of wheat in Pakistan. Information of various earliness and yield related traits are pre-requisite to develop early maturing and high yielding cotton cultivars. Therefore, the present research was conducted to determine the heterotic potential for six earliness and six yield related. For this purpose, 10 F1 hybrids were developed through crossing between nine upland cotton cultivars. These hybrids along with their parental lines were sown in the field conditions of Faisalabad, Pakistan. All the hybrids showed significant differences for observed traits. The maximum recorded values of heterosis for earliness index and seed cotton yield were 66.05% and 70.39%, respectively. Hybrid VH-289 × AGC-501 showed maximum significant heterosis (66.05%), heterobeltiosis (50.43%) and standard heterosis (32.52%) for earliness index was due to the negative heterosis in days to flowering, days to first boll opening, node number for first fruiting branch and height of first fruiting branch. Hybrid ARK-3 × AGC-501 showed maximum significant heterosis (70.39%), heterobeltiosis (28.52%) and standard heterosis (72.01%) for seed cotton yield was due to the positive heterosis showed by its yield contributing traits. This study can be used for breeding program to develop early maturing and high yielding varieties.